Evaluation of COVID-19 fear and sleep quality in individuals with epilepsy: a cross-sectional study - Polat, Hatice; Bingol, Nuray; Ay, Eda (Frontiers in Neurology, 2025)
PurposeThe study was carried out to determine the COVID-19 fear and sleep quality of people with epilepsy.MethodsThe data of this descriptive study were collected from November 2021 to February 2022 with 92 people with epilepsy in the neurology department of a hospital in eastern Türkiye. The Descriptive Information Form, Pittsburgh Sleep Quality Index (PSQI), and COVID-19 Fear Scale were used to collect the data for the study.ResultsThe mean COVID-19 score of people with epilepsy was found to be 13.55 ± 7.95, and the mean sleep quality score was 1.67 ± 1.69. Significant differences were detected in the mean fear scores of people with epilepsy according to their working status and perceived health status. It was also found that there was a significant correlation between the duration of epilepsy and sleep quality (p < 0.05). No significant differences were detected between the seizure types, number of seizures, number of medications used, presence of comorbid diseases, and fear and sleep quality (p > 0.05). No significant relations were detected between the sleep scale and its subcomponents and the COVID-19 Fear Scale (p > 0.05).ConclusionIt was found that the COVID-19 fear levels of people with epilepsy were at a moderate level and their sleep quality was good.